Reinventing the Brazilian Sign Language Interpreter (Global Journal of Human-Social Science, 2025)
This article presents a critical reflection on the evolving role of the Brazilian Sign Language Translator and Interpreter (TIL) within the national education system. Adopting a historical lens, it traces the trajectory from the early days of predominantly voluntary and community-based interpreting-particularly in religious contexts-to the current phase marked by professionalization through academic training and legal recognition. The discussion explores the implications of this transition for the interpreter's relationship with the Deaf community, the quality of linguistic mediation, and the multifaceted demands of both technical and emotional preparedness in educational settings. The article contends that the interpreter's role must transcend mere technical neutrality, assuming an ethical, cultural, and transformative stance in promoting linguistic accessibility and inclusive education for Deaf students.
Keywords: Brazilian sign language interpreter; deafness; inclusive education; accessibility; professional training